EFFECTS OF TEMPERATURE AND CREEP ON THE PERFORMANCE OF SUBGRADE LAYER - Farhan Ibrahim, Saad; Faisal Abbas, Saja (Journal of Engineering and Sustainable Development, 2017)
The creep of clayey subgrade soils is understood to be a process of deformation progressing in time under a constant stress and temperature. Owing to the creep of subgrade layer, stress redistribution occurs with a subsequent drop of the strength, and hence decreases in the value of the safety factor of the pavement structure. In addition, the seasonal variation in temperature in the subgrade layer tends to change throughout the pavement’s life. The influence of temperature on the behavior and properties of subgrade soils influences pavement performance, and distress of pavement structures. Experimental investigation of creep in a clayey subgrade layer under constant stress, with consideration of variation of temperature and dry density is a very difficult task. Therefore, despite of urgency of the problem, little has been published on this matter. Therefore it is important to investigate, and study effects of combined temperature and creep characteristics of the response of subgrade pavement layer performance by using oedometer apparatus to analysis creep behavior of pavement layers under effect of different temperatures. Based on the results of this study it is concluded that, the increase in the temperature from 20 oC to 70oC causes an increase of (52, 55.9 and 56.1%) in the creep strain of the seventh day from applying load for soil sample, asphalt sample and combined sample, respectively.